Academic Partnerships in Global Surgery: An Overview American Surgical Association Working Group on Academic Global Surgery. Issue 3 (March 2020) - Debas, Haile; Alatise, Olusegun I.; Balch, Charles M.; Brennan, Murray; Cusack, James; Donkor, Peter; Jaffe, Bernard M.; Mazariegos, George V.; Mock, Charles; Mutiibwa, David; Numann, Patricia; Nyagatuba, John Kennedy Muma; et al.
Abstract : N/A: Most surgeons from high-income countries who work in global surgery will do so through partnerships between their institutions and institutions in low- and middle-income countries (LMICs). In this article, the American Surgical Association Working Group for Global Surgery lays out recommendations for criteria that contribute to equitable, sustainable, and effective partnerships. These include ethically engaging with the LMIC partner institution by putting its interests first and by proactively seeking to be aware of cultural issues. Formally structuring the partnership with a memorandum of understanding and clearly designating leaders at both institutions are important criteria for assuring long-term sustainability. Needs assessments can be done using existing methods, such as those established for development of national surgical, obstetric, and anesthesia plans. Such assessments help to identify opportunities for partnerships to be most effective in addressing the biggest surgical needs in the LMIC. Examples of successful high-income countries-LMIC partnerships are provided.